Employment and deadweight loss effects of observed non-wage labor costs - Giovanna Aguilar; Sílvio Rendón (Institute for the Study of Labor (IZA), 2007)
To assess the employment effects of labor costs it is crucial to have reliable estimates of the labor cost elasticity of labor demand. Using a matched firm-worker dataset, we estimate a long run unconditional labor demand function, exploiting information on workers to correct for endogeneity in the determination of wages. We evaluate the employment and deadweight loss effects of observed employers' contributions imposed by labor laws (health insurance, training, and taxes) as well as of observed workers' deductions (social security, and income tax). We find that non-wage labor costs reduce employment by 17% for white-collars and by 53% for blue-collars, with associated deadweight losses of 10% and 35% of total contributions, respectively. Since most firms undercomply with mandated employers' and workers contributions, we find that full compliance would imply employment losses of 4% for white-collars and 12% for blue-collars, with respective associated deadweight losses of 2% and 6%.
Keywords: 330; Personalzusatzkosten; Arbeitsnachfrage; Excess Burden; Beschäftigungseffekt; Peru